Solve all your doubts with Teachoo Black (new monthly pack available now!)

Examples

Example 1

Example 2 Important

Example 3 Important

Example 4

Example 5 Important Deleted for CBSE Board 2023 Exams

Example 6 Important Deleted for CBSE Board 2023 Exams

Example 7 Deleted for CBSE Board 2023 Exams

Example 8 Important Deleted for CBSE Board 2023 Exams

Example 9 Deleted for CBSE Board 2023 Exams

Example 10 Important Deleted for CBSE Board 2023 Exams

Example 11 Important Deleted for CBSE Board 2023 Exams

Example 12 Deleted for CBSE Board 2023 Exams

Example 13 Important Deleted for CBSE Board 2023 Exams

Example 14 Important Deleted for CBSE Board 2023 Exams You are here

Example 15 Important Deleted for CBSE Board 2023 Exams

Example 16 Deleted for CBSE Board 2023 Exams

Example 17 Important Deleted for CBSE Board 2023 Exams

Last updated at Jan. 29, 2020 by Teachoo

Example 14 Find the rth term from the end in the expansion of (x + a)n. We know that (a + b)n = nCo anbo + nC1 an–1b1 +……..+ nCn–1 (a)(n–1) .bn–1 + nCn a0 bn = an + nC1 an–1b1 + ………………………+ nC1 a1bn–1 + bn = bn + nC1 a1 bn–1 +…………………+ nC1 an–1 b1 + an rth term from end = rth term of A.P n + 1, n , n – 1 ……… from starting We know that nth term of A.P = A + (n – 1)D Here, First Term = A = n + 1 Common difference = D = n – (n + 1) = n – n – 1 = –1 rth term from end = A + (r – 1)D = (n + 1) + (r – 1) (–1) = (n – r + 2)th term from stating We know that General term of expansion (a + b)n Tr + 1 = nCr (a)n-r.br Putting r = (n – r + 2) – 1 = n – r + 1 And, a = x & b = a T(n – r + 1) + 1 = nCn – r + 1 .(x)n – [n – r + 1] . an – r + 1 = nCn – r + 1 .(x)n- n – r + 1 . an – r + 1 = nCn – r + 1 . xr – 1 . an – r + 1 Hence rth term from end is nCn – r + 1 xr – 1 an – r + 1